TOTAM: Scoped Tuples for the Ambient - Scholliers, Christophe; Gonzalez Boix, Elisa; De Meuter, Wolfgang (Electronic Communications of the EASST, 2009)
Coordination of mobile applications posses a number of issues. Devices should be able to communicate with each other without being connected with each other at the same time while maintaining privacy and limited network traffic. Current tuple based approaches solve these issues partially but none of them solves all of them. We propose a novel tuple space-based approach where tuple spaces are annotated with tuple space descriptors used to determine the scope of a tuple. The novelty of our approach lies in the use of these tuple space descriptors to determine that a tuple should be propagated before it is transmitted. This enhances privacy and decreases the burden on the network traffic in a wide range of applications.